Investigating layer-by-layer chitosan-dextran sulfate-coated mesoporous silica as a pH-sensitive drug delivery system - Mohammad Reza Hooshyar; Shahram Raygan; Rouhollah Mehdinavaz aghdam (Journal of Materials Science: Materials in Medicine)
Abstract Mesoporous silica nanoparticles (MSNPs) coated by chitosan (CS) were shown to be a proper candidate as a carrier for drug delivery purposes. However, choosing the suitable drug-containing complexes to be applied on MSNPs-CS is of much greater importance to evaluate the possible candidate for an efficient combination of cell viability, drug release kinetics, and atherosclerosis prevention. In this regard, this study concentrates on the synthesis and assessment of coated MSNPs-CS designed for drug delivery purposes. The MSNPs are coated with polyelectrolyte complexes (PEC) composed of CS and dextran sulfate (MSNPs-CS-DX), serving as a versatile drug carrier with favorable biological characteristics. CS-DX is applied to MSNPs without requiring complex or multi-step synthesis procedures. Rosuvastatin, a cholesterol-lowering medication, is chosen for its therapeutic relevance. Additionally, CS-DX is found to relatively impede the uptake of low-density lipoproteins (LDLs) by macrophages, enhancing their potential therapeutic utility. FTIR pattern, FESEM, and TEM images prove MSNPs-CS-DX formation. DLS measurement demonstrates the average particle size of 110 nm for MSNPs, with the combined thickness of CS and DX layers ranging from 10 to 15 nm. BET test is carried out to evaluate the pore size and porosity of structure, showing outstanding results that cause an entrapment efficiency of 57% for MSNPs-CS-DX. Furthermore, the findings demonstrate the pH sensitivity of MSNPs-CS-DX on drug release kinetics. Notably, the CS-DX layer exhibits a significant enhancement in cell viability of human umbilical vein endothelial cells (HUVEC) by approximately 24% within a 24 h timeframe compared to MSNPs lacking CS-DX. Graphical Abstract